Predicting Medical Adherence based on Attachment Styles by Considering the Mediating Role of Emotional Regulation in Patients with Chronic Peptic Ulcer Disease - Abbas Keyvanloo; Aliakbar Saremi; Reza Nouri (پژوهش‌های کاربردی روانشناختی, 2025)
The purpose of this study was to investigate the prediction of medical adherence in patients with chronic peptic ulcers by examining the mediating function of emotional regulation in relation to attachment styles. The current research was fundamental in terms of its purpose and employed a correlational approach through structural equation modeling. The statistical population of the current research comprised all patients with peptic ulcers who were referred to the specialized polyclinics and personal offices of internal medicine specialists in Mashhad during the final six months of 2021. The sample consisted of 150 cases that were selected through a voluntary and intentional process. The revised version of the adult attachment scale (RAAS), Morisky medical adherence scale (MMAS), and difficulties in emotional regulation scale (DERS) were completed by the subjects. The data was analyzed using structural equation modeling. SPSS-20 and SmartPLS-3 statistical software were employed to conduct the data analysis. These findings indicated that attachment patterns have a significant indirect effect on medical adherence. Emotional regulation played a significant mediating role in this context (p<0.05). The prevalence of secure attachment styles was positively correlated with an increase in medical adherence, and individuals with higher emotional regulation reported a higher level of medical adherence. Insecure attachment styles had a significant negative effect on medical adherence; while the effect of secure attachment styles on medical adherence was direct and significant.